Value of the Systemic Immune-Inflammatory Index (SII) in Predicting the Prognosis of Patients With Peripartum Cardiomyopathy - Zhang, Yuan; Liu, Wenzhao; Yu, Huaitao; Chen, Zhen; Zhang, Chunmei; Ti, Yun; Bu, Peili (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background Peripartum cardiomyopathy (PPCM) is a potentially life-threatening complication of pregnancy. The identification of early prognostic markers in patients diagnosed with PPCM is very important. The systemic immune-inflammation index (SII) is a new inflammatory biomarker, and the aim of this study was to evaluate the prognostic value of SII in patients with PPCM. Methods A total of 61 patients with PPCM who were admitted in our hospital from 2015 to 2020 were retrospectively analyzed in this study. The follow-up period of all patients was at least 6 months after diagnosis. Recovery of left ventricular (LV) systolic function was defined as the presence of left ventricular ejection fraction > 45%. The second endpoint was defined as composite adverse cardiac events, including cardiac death or hospitalization due to worsening heart failure. Univariate and multivariate logistic regression analysis were used to determine the independent predictors of non-recovery of LV systolic function. The receiver operating characteristic (ROC) curve analysis was used to establish an cut-off level of SII value to predict persistent LV systolic dysfunction. Results The follow-up duration was 40.5 ± 16.3 months. Among the 61 patients, 43 patients showed left ventricular recovery and 18 patients did not at the last follow-up visit. The baseline SII levels were significantly higher in the nonrecovery group (P<0.05). Multivariate logistic regression showed that the SII and left ventricular end-diastolic dimension (LVEDD) were independent predictors of persistent LV systolic dysfunction (OR: 1.177, 95% CI: 1.038-1.335, P=0.011 and OR: 1.148, 95% CI: 1.011-1.304, P=0.033 respectively). A SII value of 876 was the best cut-off value (the area under the curve was 0.791, 95% CI:0.667-0.915, P<0.05), and the sensitivity and specificity were 73% and 71%, respectively. Conclusions The SII and LVEDD are independent prognostic factors for persistent LV systolic dysfunction in patients with PPCM. The SII may be a useful tool for identifying high-risk PPCM patients.